2008
DOI: 10.1007/s11162-008-9094-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Faculty Attitudes Toward Technology, Distance Education, and Innovation

Abstract: Distance education plays an important role in broadening educational access and increasing higher educational opportunities. The success, however, for any distance education initiative relies on a critical and core resource, namely having participating faculty who provide quality instruction. This study uses survey design and diffusion of innovation theory to examine faculty participation in relation to their technology use, their attitudes toward technology and distance education, and their adoption of innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
88
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 39 publications
4
88
5
3
Order By: Relevance
“…Rather, it has focused on how it affects faculty member willingness to use IT. The results of this research are consistent with studies conducted by Tabata and Johnsrud (2008) and Wang (2009). These studies found no significant relationship between faculty adoption of IT and complexity perceptions.…”
Section: Connection To the Literaturesupporting
confidence: 89%
See 3 more Smart Citations
“…Rather, it has focused on how it affects faculty member willingness to use IT. The results of this research are consistent with studies conducted by Tabata and Johnsrud (2008) and Wang (2009). These studies found no significant relationship between faculty adoption of IT and complexity perceptions.…”
Section: Connection To the Literaturesupporting
confidence: 89%
“…For example, Aremu et al (2013) and Sayadian et al (2009) found that relative advantage positively impacts faculty IT adoption, and Bennett and Bennet's (2003) research suggested that relative advantage positively influences faculty training program effectiveness. Conversely, Tabata and Johnsrud (2008) found an association between relative advantage and a decreased use of new technology practices. According to Tabata and Johnsrud, this may be because while faculty members perceive that distance education affords a relative advantage over current approaches, they do not believe that distance education instruction coincides with their responsibilities, needs, or values.…”
Section: Connection To the Literaturementioning
confidence: 88%
See 2 more Smart Citations
“…Como en muchas otras áreas de la vida moderna, la tecnología ha tenido un importante impacto en la educación superior (Meister, 1999) y, a pesar de que es obvio que esta ha experimentado fuertes y sin precedentes desafíos a partir del impacto de las tecnologías de la información -que afecta una multiplicidad de actividades y funciones institucionales (Tabata y Johnsrud, 2008)-, existe escasa evidencia acerca de cómo se relacionan estos cambios y las percepciones en torno a ellos, con la gestión del aseguramiento de la calidad.…”
unclassified